PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA POP UP BOOK TERHADAP PENINGKATAN KREATIVITAS SISWA PADA TEMA 8 KELAS 5 SDN 1 MAYONG KIDUL - Nabila Elmanidar; Fina Fakhriyah; Wawan Shokib Rondli (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Conventional learning using the lecture method can lead to low student creativity. To find out student creativity, there needs to be encouragement from the teacher.  From the observation of the preliminary study, the level of creativity of 5th grade students based on creativity indicators was 56.25%. The problem in this study is how PJBL learning can improve student creativity. This research will be conducted in grade 5 SDN 1 Mayong Kidul with 32 students as research subjects. This type of research is an experiment (pre-experimental design). Project Based Learning learning assisted by Pop Up Book media can increase student creativity as evidenced by an increase in the average pretest posttest score which has increased by 26.1%, and the N-gain test results are 0.52 with moderate criteria. So from the results of the study it can be concluded that Project Based Learning learning assisted by Pop Up Book media can increase student creativity.